PENERAPAN MODEL PEMBELAJARAN INDEX CARD MATCH TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 4 TANJUNG RAYA - Alfarini Octaliana (Jurnal Edukasi dan Penelitian Matematika, 2022)
The abilities for communicate mathematically is also one of the objectives math knowledge. However, class IX students at SMP Negeri 4 Tanjung Raya still struggle to communicate mathematical ideas. This study's goal was to ascertain if pupils who learnt using the Index Card Match model at SMP Negeri 4 Tanjung Raya had a better understanding of mathematical concepts than students who learned using standard learning methods.Quasi-experimental research design with a non-equivalent..posttest-only control group design was employed in this topic. However according analysis of data, it was determined that in class IX.of SMP Negeri 4 Tanjung Raya, students who learned using the Index Card Match model had superior mathematical communication abilities than those of students who studied using traditional learning methods.Keywords– Cooperative, Index Card Match, Communicate Mathematical